Odpływ rzeczny w zlewni górnej i środkowej Odry w różnych fazach oscylacji północnoatlantyckiej - Wrzesiński, Dariusz; Waszczak, Karolina; Plewa, Katarzyna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2016)
The study area covers watersheds in the upper and middle parts of the Oder basin down to Słubice. This region is interesting in terms of its diverse climatic, hydrological, geomorphological and environmental conditions. The study contains hydrometric data from 94 gauging stations located on 53 rivers from 1971 to 2010. Calculations were made of the outflow for the entire period in question as well as for years with high and low values of the winter NAODJFM index. On the basis of a test of the significance of differences in the outflow between the average period and the years in positive and negative phases of the NAODJFM, the effects of the changes in the intensity of the North Atlantic Oscillation on the flow of the rivers in the basin of the upper and middle Oder were examined. In a negative NAODJFM phase, in 90 catchments the outflow was above the average. In a positive NAODJFM phase, the annual outflows on most rivers were below the average. 7 317 329 23 Badania Fizjograficzne